The variation in hectolitre weight of wheat grain fed with or without enzyme supplementation influences nutrient digestibility and subsequently affects performance in pigs. Issue 2 (14th December 2018) - Clarke, Louise C.; Sweeney, Torres; Duffy, Sarah K.; Rajauria, Gaurav; O'Doherty, John V.
Abstract: A 2 × 2 factorial experiment was conducted to investigate the effect of feeding a wheat‐based diet of two different hectolitre weights (66 vs. 74 kg/hl), achieved through different agronomical conditions, with or without the supplementation of a β‐glucanase and β‐xylanase enzyme mix on young pigs. The parameter categories which were assessed included growth performance, coefficient of apparent total tract digestibility (CATTD), faecal consistency, faecal microbial populations and faecal volatile fatty acid (VFA) concentrations. Sixty‐four pigs (11.6 kg SD 0.97) were assigned to one of four dietary treatments: (T1) low hectolitre weight wheat diet, (T2) low hectolitre weight wheat diet containing 0.1 g/kg β‐glucanase and β‐xylanase enzyme supplement, (T3) high hectolitre weight wheat diet and (T4) high hectolitre weight wheat diet containing 0.1 g/kg β‐glucanase and β‐xylanase enzyme supplement. The inclusion of wheat was 500 g/kg in the diet. The low hectolitre weight grain had a higher level of zearalenone, aflatoxin and ochratoxin contamination compared to the high hectolitre weight grain. The high hectolitre weight wheat had a higher gross energy (GE), crude protein (CP) and lysine contents compared to the low hectolitre weight wheat. Pigs offered the low hectolitre weight diet had a lower average daily gain (ADG) ( p < 0.001), a lower gain to feed (G:F) ratio ( p < 0.001) and a higher faecal score (more diarrhoea) ( p < 0.001) compared to pigs offered the high hectolitre weight. The low hectolitre weight diet had a reduced CATTD ( p < 0.05) of nitrogen (N) and gross energy (GE) compared with pigs offered the high hectolitre weight diet. In conclusion, the higher level of mycotoxins and lower content of GE, CP and lysine in the low‐quality wheat reduced ADG and the CATTD of nutrients in pigs offered this diet. The inclusion of a β‐glucanase and β‐xylanase enzyme mix had no effect on growth performance or nutrient digestibility.